Enrichment devices for undocked heavy pigs: effects on animal welfare, blood parameters and production traits. Issue 1 (2nd January 2019) - Nannoni, Eleonora; Sardi, Luca; Vitali, Marika; Trevisi, Erminio; Ferrari, Annarita; Ferri, Michela E.; Bacci, Maria L.; Govoni, Nadia; Barbieri, Sara; Martelli, Giovanna
Abstract: Two independent trials were carried out to test the effectiveness of different environmental enrichments in improving Italian heavy pigs' welfare. Eighty undocked Landrace × Large White barrows (body weight range: 27.1–158.4 kg) were used. In Trial 1, group C1 received a metal chain and group WL wooden logs (placed inside a specifically designed metal rack). In trial two, the enrichments proposed were a hanging chain (C2), and a vegetal edible block (EB) inside the metal rack. General health, animal behaviour, hair cortisol, blood parameters and growth performance were recorded. In Trial 1, WL pigs interacted with the enrichment at a lower extent than C1 ( p < .01) and walked less ( p < .05). In Trial 2, EB pigs spent less time in lateral recumbency and rooting/exploring the pen floor ( p < .05 and p < .01, respectively), and interacted more with the enrichment ( p < .001) than C2. Motivation to explore both WL and EB was maintained over time, conversely to what happened to C1 and C2. No differences were observed in hair cortisol concentration, neutrophil/lymphocyte ratio, skin lesions and growth parameters. Tail lesions were higher in WL than in C1 ( p < .05) Minor, transient differences were found in plasma biomarkers. Overall, WL had limited effect on behaviour, whereas EB might have reduced floor over-exploration when compared to the chains. It is concluded that, although from an animal behaviour standpoint EB might be promising, regardless of the device used (C, WL or EB), all experimental groups showed similar welfare parameters levels, stimulating the necessity for wider research on enrichment design and function.